Penerapan Model Pembelajaran Kooperatif Team Quiz Untuk Meningkatkan Ketrampilan Berbicara Bahasa Arab Siswa Kelas X - Umi Adibah (Lembaga Sosial Rumah Indonesia, 2021)
Learning Arabic speaking skills is very important in improving students' ability to speak Arabic. This study aims to explore how to learn Arabic by using a team quiz cooperative model to improve speaking skills in Arabic class X MIPA 3 MAN 2 Bantul. This research is a classroom action research conducted on students of class X MIPA 3 MAN 2 Bantul from January to March of the 2019/2020 school year. The results of this study indicate that the team quiz cooperative learning model is significantly able to improve students' Arabic speaking skills, students are more actively involved in the process of learning Arabic speaking skills with an orderly and fun class design. The application of the team quiz cooperative learning model makes it easier for students to understand the lesson and more easily capture new vocabulary and express it again because students are trained to speak Arabic directly with the team quiz cooperative learning model.